0041 Collaboration multiplier: advancing multi-sector partnerships to prevent violence. (26th April 2015) - Davis, Rachel; Tsao, Benita
Abstract : Statement of purpose: Violence injures, maims and kills people before their time, and it undermines efforts to help young people succeed in life. Given the range and complexity of the root causes of violence, no single agency can prevent violence on its own, yet these fields often don't realise what difference they can make and aren't sure how to be most effective. Methods/Approach: The Collaboration Multiplier tool has a long track record of success, and Prevention Institute has used it to facilitate diverse groups for more than a decade. To adapt this tool for preventing violence, Prevention Institute conducted a literature review, a scan of 10 municipal websites, and more than 30 in-depth interviews with practitioners in 14 large U. S. cities and counties. Representatives of various sectors reviewed specific chapters and provided feedback. Results: Multi-Sector Partnerships for Preventing Violence walks readers through the two phases of Collaboration Multiplier—Information-Gathering and Analysis—in order to identify shared outcomes, collective strengths and joint strategies. This guide clarifies the roles and contributions of 10 public and private sectors and 12 municipal departments as it relates to preventing violence—from libraries and workforce development, to social services and public works. The guide features case examples, talking points to persuade others to get involved and suggested actions for them, an introduction to the public health approach to preventing violence, and activities for each step of the Collaboration Multiplier tool. Conclusions: Mobilising diverse stakeholders to work together is critical to advancing community safety. When people collaborate to address the risk and resilience factors for violence, they can accomplish ambitious goals and have an impact that no organisation could achieve through a stand-alone effort. Creating safe communities requires the active involvement of many public sectors and community stakeholders working in tandem. Significance and contribution to the field: Multi-sector collaboration is critical for preventing violence, and cities with greater collaboration among multiple sectors have lower rates of violence. This guide was designed to help violence prevention practitioners engage partners from diverse sectors and disciplines, strengthen their efforts, and replicate the Collaboration Multiplier process for their communities.